The Nomadic Office: A Location Independent Workspace Through Mixed Reality - Knierim, Pascal; Kosch, Thomas; Schmidt, Albrecht (IEEE pervasive computing, 2021)
The worldwide spread of the coronavirus forcefully affected our lives, the economy, and social culture. Unforeseen, a significant number of workforces are requested or required to work from home, impacting creativity, work performance, and social interaction. Video conferencing tools are consequently substituting in-person meetings; new workplaces are arranged in domestic environments, causing a shift in how employees work and interact with their environment. At the same time, recent developments in mixed reality (MR) enable us to synthesize virtual office environments and experience them on the go. This article consolidates how the latest research in MR supports the transition of desktop computing into the virtual realm, enriching traditional office environments with virtual elements. We conceptualize augmented domestic workspaces and truly nomadic offices that overcome the physical constraints and unfavorable effects of continuous telecommuting. To promote future research, we highlight open research questions and outline a nomadic MR office of the future.